Linguistics incivility in student: Lecturer communication on WhatsApp - Rohali, Rohali; Tobing, Roswita Lumban; Perdi Rahayu, Siti (LingTera, 2024)
This research aims to identify (1) strategies of linguistic incivility used in student-lecturer communication, and (2) the aspects of speech acts used that represent linguistic incivility. The research analyzed data from six WhatsApp groups that include students and lecturers. The distributional method was used to analyze linguistic incivility representations and the identity method to analyze linguistic incivility strategies. The results demonstrated that the incivility strategies used include (1) respecting other people's time (34%), (2) asserting oneself (19%), (3) refraining from idle complaints (16%), (4) speaking kindly (9%), (5) listening (6%), (6) respecting even a subtle "no" (6%), (7) respecting others' opinions (6%), and (8) not shifting responsibility and blame (3%). Furthermore, students violated the rules of linguistic civility by these actions: initiating conversations without greetings, using excessive words, expressing personal complaints, conveying opinions impolitely, and shifting blame. Recognizing the importance of linguistic civility in student-lecturer communication is crucial for fostering respectful and productive interactions.